Interband plasmonic nanoresonators for enhanced thermoelectric photodetection - Zamiri Golnoush; Wredh Simon; Rahman Md Abdur; Adanan Nur Qalishah; Vu Cam Nhung; Wang Hongtao; Arora Deepshikha; Sugiyama Haruya; Kubo Wakana; Dong Zhaogang; Simpson Robert E.; Yang Joel K.W. (Nanophotonics)
Thermoelectric photodetectors are robust alternatives to photodiodes with applications in extreme environments; however, the poor absorptivity of thermoelectric materials limits their photosensitivity. Here, we take a new look at the traditional thermoelectric materials Sb2Te3 and Bi2Te3 in their recently discovered ability to support interband plasmonic resonances in the visible spectrum. We fabricated nanoresonators directly into the thermoelectric materials to improve their optical absorptance through plasmonic field enhancements, leading to improved photo-thermoelectric conversion. A thermoelectric detector with Sb2Te3 and Bi2Te3 nanostructures demonstrated ∼90 % optical absorptance across the visible spectrum, more than twice that of unpatterned materials. The solid-state device was fabricated on a substrate and exhibited a response time of 160 µs and a specific detectivity of 3.2×106cm Hz12W−1 $\left.3.2{\times}1{0}^{6} \text{cm\,H}{\text{z}}^{1/\right.2} {\text{W}}^{-1}$ . Our demonstration that plasmonic and thermoelectric properties can be exploited within the same material could advance photodetectors and other optoelectronic technologies, such as biosensors, solar cells, and integrated spectrometers.